Aktivitas Antihiperkolesterolemia Ekstrak Etanol Daun Stevia Rebaudiana Bertoni Pada Tikus Putih Jantan - meta kartika untari; Ganet Elo Pramukantoro (Journal Syifa Sciences and Clinical Research, 2020)
Hypercholesterolemia is a state of increased levels of LDL (Low Density Lipoprotein) and total cholesterol in the plasma. Stevia leaves have benefits to overcome hypercholesterolemia. The aimed of this study was to obtain ethanol extracts of Stevia rebaudiana Bertoni leaves which have activity to reduce total cholesterol levels in patients with hypercholesterolemia with effective doses. The method that will be carried out to achieve this goal was to make extracts by maceration of Stevia rebaudiana Bertoni leaf powder using a water solvent for 5 days. Testing antihypercholesterolemia activity by giving treatment to 20 male white rats. Rats were divided into 5 treatment groups. Group I was negative control, II was simvastatin control, III extract was 30 mg / 200 g BW, IV extract was 60 mg / 200 g BW, V extract was 120 mg / 200 g BW. The mice were induced by propylthiouracil 12.5 mg / day and high-fat feed for 21 days, after which the rats were given the test for 14 days. Cholesterol levels were measured on days 0, 21st and 28th. The method of determining cholesterol levels uses the Easy Touch tool. On the 35th day, a total cholesterol level was examined and data analysis was performed. The results showed that the ethanol extract of stevia leaves had antihypercholesterolemia activity, extract dose of 30 mg / 200 g BW had antihypercholesterolemia activity which was equivalent to simvastatin.